Palladium-Catalyzed Synthesis of Diarylamines and 1- and 2-Oxygenated Carbazoles: Total Syntheses of Natural Alkaloids Clauraila A, Clausenal, Clausine P, and 7-Methoxy-O-methylmukonal - Hernández-Benitez, R. Israel; Zárate-Zárate, Daniel; Delgado, Francisco; Tamariz, Joaquín (Synthesis, 2017)
The scope and limitations of the strategy for the conversion of 2-anilinocyclohexenones and N-arylcyclohexane enaminones into the 1- and 2-oxygenated carbazole scaffolds, respectively, were evaluated. The one-pot palladium(0)-catalyzed aromatization/methylation process of the aforementioned substrates provided a diversity of the corresponding diarylamines. A subsequent palladium(II)-catalyzed cyclization of the latter delivered the desired 1- and 2-oxygenated carbazoles in good overall yields. Special attention was given to the synthesis of the uncommon 1,8-disubstituted carbazoles. This methodology was employed for the total synthesis of the naturally occurring clauraila A, clausenal, clausine P, and 7-methoxy-O-methylmukonal.
Keywords: 1- and 2-oxygenated carbazoles; diarylamines; palladium(II) coupling; clausenal; clausine P